Effectiveness of negative pressure wound therapy on chronic wound healing: A systematic review and meta-analysis - Asmat Burhan; Nizam bin Ali Khusein; Septian Mixrova Sebayang (Belitung Nursing Journal, 2022)
Background: Negative Pressure Wound Therapy (NPWT) is considered an effective treatment in facilitating the healing of chronic wounds. However, its effect remains inconsistent, which allows for further investigation. Objective: This study aimed to assess the effectiveness of the NPWT program in improving the management of chronic wound healing. Design: Systematic review and meta-analysis was used. Data Sources: The search strategy ranged from 2016 to 2021 in PubMed, CINAHL, ProQuest, and ScienceDirect. Review Methods: Risk of bias was done based on the Risk of Bias 2.0 guideline using RevMan 5.4.1, and meta-analysis was done using Jeffreys’s Amazing Statistics Program (JASP) software version 0.16.3. Critical appraisal of the included articles was done according to Joanna Briggs Institute’s (JBI) appraisal checklist. Results: A total of 15 articles were included, with 3,599 patients with chronic wounds. There was no publication bias in this study seen from the results of the Egger’s test value of 0.447 (p >0.05), symmetrical funnel plot, and fail-safe N of 137. However, heterogeneity among studies was present, with I2 value of 66.7%, Q = 41.663 (p <0.001); thus, Random Effect (RE) model was used. The RE model showed a significant positive effect of the NPWT on chronic wound healing, with z = 3.014, p = 0.003, 95% CI 0.085 to 0.400. The observed effects include decreased rate of surgical site infection, controlled inflammation, edema, and exudate, as well as increased tissue with varying forest plot size, as demonstrated by the small effect size (ES = 0.24, 95% CI -0.26 to 0.79, p <0.05). Conclusion: The analysis results show that the standard low pressure of 80-125 mmHg could improve microcirculation and accelerate the healing process of chronic wounds. Therefore, applying the NPWT program could be an alternative to nursing interventions. However, it should be carried out by competent wound nurses who carry out procedure steps, implement general patient care, and give tips on overcoming device problems and evaluation. PROSPERO registration number: CRD42022348457